KAJIAN VISUAL KERAGAMAN CORAK PADA KAIN ULOS - Yana Erlyana (Universitas Trisakti, 2016)
AbstractEach pattern that visualize on ulos has a different meaning. The patterns on the fabric not only appear as a decoration of the fabric but has a visual stylized of biodiversity that are associated with the function itself. This study aims to reveal the stylized depiction of biodiversity on ulos and the meanings that associated with the function of the fabric. Based on the documentation of ulos pattern from Batak tribe of North Sumatra, ranging from the physical analysis, visual stylized to the meanings, symbols and the role of the image of the pattern. Thus this study may be a form of Indonesia cultural preservation, as well as visual references for research and the creation of subsequent works, especially works made under the inspiration of art and cultural traditions.AbstrakSetiap corak pada kain ulos memiliki pemaknaan gambar yang berbedabeda. Corak pada kain ulos tidak hanya tampil sebagai hiasan pada kain tetapi memiliki stilasi visual dari keanekaragaman hayati yang dikaitkan dengan fungsinya. Kajian ini bertujuan mengungkap penggambaran stilasikeanekaragaman hayati pada kain ulos dan pemaknaan yang dikaitkan dengan fungsi kain. Berdasarkan dokumentasi corak kain ulos suku Batak Sumatra Utara, dilakukan analisa mulai dari fisik, gaya stilasi hingga makna, simbol dan peranan gambar tersebut. Dengan demikian kajian ini dapat menjadi bentuk pelestarian kebudayaan Indonesia, serta referensi visual bagi penelitian maupun penciptaan karya selanjutnya, terutama karya-karya yang dibuat berdasarkan inspirasi seni budaya tradisi.